Congenital multiple infantile myofibromatosis. - Patrizi, A.; Bianchi, F.; Neri, I.; Trestini, D. (European Journal of Pediatric Dermatology, 2001)
Infantile myofibromatosis is a rare congenital fibrous tumor of infancy, characterized by single or multiple nodules of the skin, bones and viscera. This paper reports a case of congenital multiple myofibromatosis observed in a 2-month-old boy. The case demonstrates the good prognosis of these forms.